Modern conceptions of serological tumor markers and their role in oncology - N. S. Sergeeva (Uspehi Molekulârnoj Onkologii, 2015)
The paper reviews modern concepts of serological tumor markers and their place in oncology: using for differential diagnostics, in the prognosis of the tumor, follow-up and for preclinical revealing of relapses, as well as in the screening aimed at early detection of malignant neoplasms. Biochemical characteristics and functions of most informative tumor markers (CA125, PSA etc.) were described. Currently diagnostic indexes, obtained by the in vitro diagnostic multivariate index assay (IVDMIA), and algorithms using several serological markers begin to apply in laboratory practice to increase diagnostic accuracy. Also some promising new serological tumor markers were described in this review.